A new approach for harmonic elimination in single-pulse modulated single-phase inverter drive system - Sünter, Zeliha; Altun, Hüseyin; Sünter, Sedat (Gazi Universitesi Muhendislik-Mimarlik, 2015)
In this paper, a novel control technique which is a particular implementation of the quasi square wave method has been proposed for a single-phase inverter drive. With the proposed control technique, 3rd and 3rd order harmonics together with even harmonics of the inverter output voltage waveform are eliminated as in a six-step inverter. An output voltage waveform with less harmonic content for one output period of the inverter operation is produced using the same switching rate as that of quasi square wave method. Output voltage control is performed by using a variable DC link inverter. Matlab/Simulink models of the proposed system, and the inverter system with quasi square wave modulation technique have been obtained. The comparative simulation results for both techniques are given at various output frequencies. Open-loop V/f control has been applied to both inverters feeding an R-L load, V/f controlled inductive and single-phase induction motor loads. Superiority of the proposed technique to the conventional quasi square wave modulation technique has been shown with the output waveforms and their spectra.
Tek-darbe modülasyonlu bir fazli evirici sürücü sisteminde harmonik eliminasyonu için yeni bir yaklaşim
Keywords: Quasi square wave; Single-phase inverter; Single-pulse modulation; Total harmonic distortion (THD)